Geochemical baseline soil surveys for understanding element and isotope variation across New Zealand. Issue 3 (3rd July 2018) - Rattenbury, Mark; Martin, Adam; Baisden, Troy; Turnbull, Rose; Rogers, Karyne
ABSTRACT: Systematic grid-based soil geochemical baseline surveys have been undertaken in the South Island since 2013 at regional scales in Southland, Otago, Buller, Nelson and Marlborough and more detailed scales such as in Dunedin City and Nelson's Richmond Range. More than 1300 sites and 3000 samples have now been analysed for their chemical element composition, supported by rigorous quality control procedures. The initial data interpretation shows strong underlying rock control on soil chemistry and localised anthropogenic input, principally in urban areas and through fertiliser application in higher intensity farming areas. The technical success and potential multi-use application of these surveys provide an argument for undertaking a national systematic geochemical baseline survey designed around international best practice.